거시경제 및 통화정책 기조 변화가 통화정책의 유효성에 미친 영향 분석 - 김태봉 (13777, 2014)
This paper has studied the monetary policy in Korea with a time varying VAR model using four key macroeconomic variables. First, inclusion of the exchange rate was a crucial factor in evaluating Korean monetary policy since the monetary policy demonstrate